Transient Depletion of CD169+ Cells Contributes to Impaired Early Protection and Effector CD8+ T Cell Recruitment against Mucosal Respiratory Syncytial Virus Infection - Oh, Dong Sun; Oh, Ji Eun; Jung, Hi Eun; Lee, Heung Kyu (Frontiers in Immunology, 2017)
Respiratory syncytial virus (RSV) is a major cause of respiratory viral infections in infants and children. Alveolar macrophages (AMs) play a crucial role in combatting airborne pathogens, strongly express CD169, and are localized in the lung alveoli. Therefore, we used CD169-diphtheria toxin receptor (DTR) transgenic mice to explore the roles of CD169+ cells in immune responses to mucosal RSV infection. The administration of diphtheria toxin to CD169-DTR mice induced specific AM depletion and reduced the recruitment of Ly6Chi monocytes. Notably, CD169+ cell depletion reduced levels of innate cytokines, such as IFN-β, IL-6, and TNF-α, in bronchoalveolar lavage fluid during RSV infection without affecting the production of proinflammatory chemokines. Moreover, the depletion of CD169+ cells increased the recruitment of inflammatory cells to the lung during the early stage of RSV infection, although not during the later stages of RSV infection. Furthermore, the depletion of CD169+ cells reduced the recruitment of effector CD8+ T cells to the lungs after RSV mucosal infection. Our findings suggest that modulating the number of CD169+ cells to enhance immune responses to RSV infection may be useful as a new therapeutic strategy.